Comparação entre os efeitos da associação gelatina-resorcina-formaldeído e do n-butil-2-cianoacrilato na síntese do parênquima hepático de coelhos - Silveira, Lucia Maria Guedes (2005)
There are difficulties in liver surgical procedures, specifically hemostasis, due to anatomic and functional characteristics of this organ. Considering these factors, this study compared the effect of two surgical adhesives, gelatin-resorcin-formaldeíde and n-butil-2-cianoacrilate, in the liver synthesis. Clinical evolution of the animals utilized in this study and cicatrization of experimental liver surgical wounds were investigated. Cicatrization was analysed by macroscopic and microscopic evaluation. Results demonstrated fast and efficient hemostasis in both groups, and more important cellular and tissue alterations on the animals treated by n-butil-2-cianoacrilate, when this group was compared to the control and gelatin-resorcin-formaldeíde groups. Considering the purpose of this study, gelatin-resorcin-formaldeíde compound was the best alternative method on cases where the sutures employed alone had failed to provide adequate hemostasis.